Kepemimpinan Model Gembala - Klau, Yohana Aek (JURNAL PROPHETA, 2021)
The article elaborates that Pastoral leadership is a leadership model offered as asolution to today's Christian leadership problems. When many leadership trends thatemerge today cannot satisfy the people, the theory of pastoral leadership has receivedextensive study and has also been applied in secular leadership in companies around theworld. Moreover, the study of pastoral leadership talks about the principle of servantleadership, in which the leader's character, such as kindness, sincerity, skill, and loyalty,has become a much-needed principle in leadership that has begun to shift toauthoritarian principles and be served. This study finds and confirms that if this pastoral leadership practice is practiced, it can be ascertained that there will be a successful andtransformative leadership for the church and society.